1983
DOI: 10.1007/bf00378426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of occupational mercury exposure on plasma lysosomal hydrolases

Abstract: The activities of three plasma lysosomal hydrolases, beta-galactosidase, beta-glucuronidase and beta-N-acetylglucosaminidase, were studied in 20 workers exposed to metallic mercury vapor in a chlorine alkali plant and in 10 nonexposed referents. The urinary excretion and blood levels of mercury were determined on the day of study, and the history of mercury exposure was reviewed from the records of mercury concentrations in urine and blood over periods of up to 133 months. The average levels of beta-N-acetylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…We lacked statistics on the number of dental fillings in individuals in the sample, which prevents us from adjusting for this variable. Nevertheless, it has been suggested that there is not sufficient evidence that methylation of inorganic mercury is produced in live human organisms 39 , in spite of the fact that some studies 985 Mercury uptake and fish consumption do indicate this 40,41 . Furthermore, methylmercury may undergo a low-intensity process of demethylation and turn into inorganic mercury.…”
Section: Discussionmentioning
confidence: 99%
“…We lacked statistics on the number of dental fillings in individuals in the sample, which prevents us from adjusting for this variable. Nevertheless, it has been suggested that there is not sufficient evidence that methylation of inorganic mercury is produced in live human organisms 39 , in spite of the fact that some studies 985 Mercury uptake and fish consumption do indicate this 40,41 . Furthermore, methylmercury may undergo a low-intensity process of demethylation and turn into inorganic mercury.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recall that blood, hair, and urine mercury levels reflect recent exposure and do not correlate with total body burden [83–86]. Blood and urine levels correlate fairly well to each other, but not to total body burden [87].…”
Section: Laboratory Assessment Of Mercury Exposurementioning
confidence: 99%
“…The subjects were instructed to collect all voided urine during exactly 24 h. The total mercury content of a 24-h urine sample was used for calculating the current excretion rate, which has been shown to be a stable biological index of mercury exposure (17,18).…”
Section: Subjectsmentioning
confidence: 99%
“…The only study found using the urinary excretion rate of mercury for estimating mercury exposure was that of Aitio et al (17). For a reference group of 10 individuals a mean excretion rate of 2.4 ug Hg /24 h was reported.…”
mentioning
confidence: 99%